FROM BASIC TO CONTEMPORARY SEMEN ANALYSIS: LIMITATIONS AND VARIABILITY - A. Moazzam; M. N. Choudhary; I. Muhammad; J. Sarwat; A. Ijaz (Journal of Animal and Plant Sciences, 2015)
Fertility has been a core issue for the survival of human race since pre-historic ancient times. A couple who has failed to conceive or has been unable to induce pregnancy within one year of regular unprotected intercourse in the fertile phase of menstrual cycle are said to be infertile. Of the total infertile couples who seek evaluation for infertility, a large part of infertility is accounted by the male factor A general and obvious cause of male infertility is impaired spermatozoal function. Semen analysis is the first step towards assessment of a male’s reproductive potential. Analysis of seminal parameters help in providing important clinical information regarding spermatogenesis, the functional competence of spermatozoa and also the secretory pattern of accessory genital glands. Although the clinicians base their initial diagnosis upon the fundamental information provided by analysis of these sperm parameters, yet more advanced sperm function tests are required for an exact diagnosis of the root cause of infertility in the male.
Keywords: Semen Analysis; Leukocytospermia; Computer Aided Sperm Analyzer; World Health Organization